Pendampingan Penyusunan Laporan Keuangan BUM Desa Kabupaten Ngawi - Muhammad Heru Akhmadi; Muhammad Syahrul Fuady; Dani Sugiri (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Community Service Activities are carried out with Village-Owned Enterprises (BUM Desa) partners in the Ngawi Regency environment. Service activities are carried out in the method of technical guidance for BUM Desa accounting and assistance in preparing financial reports. From the evaluation of technical guidance activities, it is known that guidance activities provide an increase in the average test scores of activity participants. Technical guidance activities have been carried out since the introduction of the BUM Desa financial report, the financial report preparation cycle and simulation of the preparation of financial statements. Participants are trained since recognizing transactions, analyzing transaction evidence, recording journals, posting ledgers, compiling trial balances, and compiling BUM Desa financial reports. The simulation was carried out either manually or using a Microsoft Excel-based application. During the discussion process, participants also conveyed many transaction cases they faced in accordance with the BUMDesa business field. The results of this community service activity can provide added value to teaching activities and community service activities in the same field regarding the need for early partner identification, a combination of learning models, and the use of more real examples of transactions as case-based studies.